Modified Poly(ethylene terephthalate) Nano Fibers for Removal of Copper(II) Ions - Azizinezhad, Fariborz (Journal of Applied Solution Chemistry and Modeling, 2019)
In this research, the adsorption of Cu2+ ions from aqueous solution was investigated by the modified poly (ethylene terephthalate) fibers as a new adsorbent. The best condition of electrospinning was recorded (voltage= 10 kV- distance from nozzle= 12.5 cm - solution convcentration= 0.2 g/mL). The optimum condition for removal of Cu2+ ions were determined (pH=10 - time= 60 min - C= 120 mg/L, qm = 62.4 mg/g). The adsorption data were best fitted by dubinin-radushkevich isotherm and pseudo-second order kinetic models, as well. Structure of the nanofibers were emphasized by scanning electron microscpy (SEM) and thermo gravimetric analysis (TGA).